Roles and regulation of membrane-associated serine proteases. (22nd May 2007) - Qiu, D.; Owen, K.; Gray, K.; Bass, R.; Ellis, V.
Abstract : Pericellular proteolytic activity affects many aspects of cellular behaviour, via mechanisms involving processing of the extracellular matrix, growth factors and receptors. The serine proteases have exquisitely sensitive regulatory mechanisms in this setting, involving both receptor-bound and transmembrane proteases. Receptor-bound proteases are exemplified by the uPA (urokinase plasminogen activator)/uPAR (uPAR receptor) plasminogen activation system. The mechanisms initiating the activity of this proteolytic system on the cell surface, a critical regulatory point, are poorly understood. We have found that the expression of the TTSP (type II transmembrane serine protease) matriptase is highly regulated in leucocytes, and correlates with the presence of active uPA on their surface. Using siRNA (small interfering RNA), we have demonstrated that matriptase specifically activates uPAR-associated pro-uPA. The uPA/uPAR system has been implicated in the activation of the plasminogen-related growth factor HGF (hepatocyte growth factor). However, we find no evidence for this, but instead that HGF can be activated by both matriptase and the related TTSP hepsin in purified systems. Hepsin is of particular interest, as the proteolytic cleavage sequence of HGF is an 'ideal substrate' for hepsin and membrane-associated hepsin activates HGF with high efficiency. Both of these TTSPs can be activated autocatalytically at the cell surface, an unusual mechanism among the serine proteases. Therefore these TTSPs have the capacity to be true upstream initiators of proteolytic activity with subsequent downstream effects on cell behaviour.